Molecular transistors as substitutes for quantum information applications. (2nd November 2022) - Dhingra, Archit; Hu, Xuedong; Borunda, Mario F; Johnson, Joseph F; Binek, Christian; Bird, Jonathan; N'Diaye, Alpha T; Sutter, Jean-Pascal; Delahaye, Emilie; Switzer, Eric D; Barco, Enrique del; Rahman, Talat S; et al.
Abstract: Applications of quantum information science (QIS) generally rely on the generation and manipulation of qubits. Still, there are ways to envision a device with a continuous readout, but without the entangled states. This concise perspective includes a discussion on an alternative to the qubit, namely the solid-state version of the Mach–Zehnder interferometer, in which the local moments and spin polarization replace light polarization. In this context, we provide some insights into the mathematics that dictates the fundamental working principles of quantum information processes that involve molecular systems with large magnetic anisotropy. Transistors based on such systems lead to the possibility of fabricating logic gates that do not require entangled states. Furthermore, some novel approaches, worthy of some consideration, exist to address the issues pertaining to the scalability of quantum devices, but face the challenge of finding the suitable materials for desired functionality that resemble what is sought from QIS devices.